Spatial distribution of Langmuir waves observed upstream of Saturn's bow shock by Cassini. Issue 8 (25th August 2016) - Píša, D.; Santolík, O.; Hospodarsky, G. B.; Kurth, W. S.; Gurnett, D. A.; Souček, J.
Abstract: We present the spatial distribution and spectral properties of Langmuir waves observed upstream of Saturn's bow shock by the Cassini spacecraft. The entire 10 kHz wideband data set obtained between June 2004 and December 2014 has been analyzed using an automated procedure. Almost 10 6 waveform snapshots with intense narrowband emissions in the frequency range of 1–10 kHz were detected. A typical wave spectrum exhibits a single intense peak (62% of all selected waveforms). However, spectra with a superposition of two (25%) or more (13%) intense peaks are also observed. Using magnetic field observations and a model of the bow shock, plasma wave activity across Saturn's foreshock has been mapped. The plasma wave occurrence increases steeply behind the tangent magnetic field line, i.e., the sunward foreshock boundary, and rises with increasing distance from the tangential line into the downstream region. The single peak spectra are observed across the entire foreshock, while more complicated spectra are more likely measured deeper inside the foreshock and closer to the bow shock. We confirm that the most intense waves occur close to the tangent point and decrease both deeper in the foreshock and along the tangential line. Key Points: Long‐term survey of plasma waves at frequencies 1–10 kHz inside Saturn's foreshock High activity of narrowband emissions maps the entire upstream region at Saturn Less intense and more complex waves are observed deeper inside the foreshock